Elegant and Innovative Recoding Strategies for Advancing Vaccine Development - François Meurens; Fanny Renois; Uladzimir Karniychuk (Vaccines, 2025)
Recoding strategies have emerged as a promising approach for developing safer and more effective vaccines by altering the genetic structure of microorganisms, such as viruses, without changing their proteins. This method enhances vaccine safety and efficacy while minimizing the risk of reversion to virulence. Recoding enhances the frequency of CpG dinucleotides, which in turn activates immune responses and ensures a strong attenuation of the pathogens. Recent advancements highlight synonymous recoding’s potential, offering improved genetic stability and immunogenicity compared to traditional methods. Live vaccines attenuated using classical methods pose a risk of reversion to virulence and can be time-consuming to produce. Synonymous recoding, involving numerous codon alterations, boosts safety and vaccine stability. One challenge is balancing attenuation with yield; however, innovations like Zinc-finger antiviral protein (ZAP) knockout cell lines can enhance vaccine production. Beyond viral vaccines, recoding can apply to bacterial vaccines, as exemplified by modified Escherichia coli and Streptococcus pneumoniae strains, which show reduced virulence. Despite promising results, challenges like ensuring genetic stability, high yield, and regulatory approval remain. Briefly, ongoing research aims to harness these innovations for comprehensive improvements in vaccine design and deployment. In this commentary, we sought to further engage the community’s interest in this elegant approach by briefly highlighting its main advantages, disadvantages, and future prospects.